Transepiphyseal (Type VII) Ankle Fracture Versus Os Subfibulare in Pediatric Ankle Injuries. Issue 10 (November 2018) - Sugi, Michelle T.; Tileston, Kali; Krygier, Jeffery E.; Gamble, James
Abstract : Background: Pediatric ankle injuries are common, giving rise to ∼17% of all physeal injuries. An os subfibulare in a child with an ankle sprain may be confused with a type VII transepiphyseal fracture. Here, we evaluate the clinical and radiographic features of type VII transepiphyseal fractures to those of os subfibulare presenting with acute ankle trauma with the hypothesis that radiographs are necessary for final diagnosis and neither clinical history nor examination would be diagnostic. Methods: We performed an internal review board-approved, retrospective chart review of patients identified with a traumatic os subfibulare or type VII ankle fracture over an 18-month period. Charts were reviewed for demographics, mechanism, and clinical findings on initial presentation. Radiographic measurements of the distal fibular fragment as well as epiphysis were made on presenting ankle series radiographs. Results: A total of 23 patients were identified. Eleven patients had a traumatic type VII ankle fracture and 12 had trauma associated with an os subfibulare on initial radiographs. The history and clinical presentations were similar and were nondiagnostic. The ratio of the width of the fibula at its largest point on the anterior posterior view to the width of the fibular fragment was significantly larger in the type VII ankle fractures ( P =0.05). All os subfibulare were located within the inferior third of the epiphysis, whereas all type VII fractures were either at the equator or within the middle third of the fibular epiphysis. Conclusions: Radiographs, not clinical presentation, can differentiate an os subfibulare from a type VII transepiphyseal fracture. Children with type VII fractures have a long, irregular fracture line within the middle third of the distal fibular epiphysis. Those with an ankle sprain and os subfibulare have a smooth-edged ossicle of relatively short length located within the inferior pole of the epiphysis. Furthermore, the radiographic width of the fragment in the type VII fractures is significantly larger in width than the os subfibulare. Level of Evidence: Level II.